2009
DOI: 10.1186/1756-8722-2-20
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1-2a multicenter dose-escalation study of ezatiostat hydrochloride liposomes for injection (Telintra®, TLK199), a novel glutathione analog prodrug in patients with myelodysplastic syndrome

Abstract: Background: Ezatiostat hydrochloride liposomes for injection, a glutathione S-transferase P1-1 inhibitor, was evaluated in myelodysplastic syndrome (MDS). The objectives were to determine the safety, pharmacokinetics, and hematologic improvement (HI) rate. Phase 1-2a testing of ezatiostat for the treatment of MDS was conducted in a multidose-escalation, multicenter study. Phase 1 patients received ezatiostat at 5 dose levels (50, 100, 200, 400 and 600 mg/m 2 ) intravenously (IV) on days 1 to 5 of a 14-day cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 6 publications
2
33
0
Order By: Relevance
“…These results confirm the previously reported proof of concept study using intravenous administration, 8 as well as the phase 1 study of the current oral formulation using an abbreviated dosing schedule. 7 The population in this study was heavily prior treated: 77% resistant to erythropoietin, 38% resistant to lenalidomide, and 47% resistant to HMAs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results confirm the previously reported proof of concept study using intravenous administration, 8 as well as the phase 1 study of the current oral formulation using an abbreviated dosing schedule. 7 The population in this study was heavily prior treated: 77% resistant to erythropoietin, 38% resistant to lenalidomide, and 47% resistant to HMAs.…”
Section: Discussionsupporting
confidence: 90%
“…The lower dose, longer exposure time dose schedule was observed to have a longer duration of response. The median time to HI-E response was 8 weeks (range, [8][9][10][11]. A 19% HI-N response rate was observed in patients with neutropenia (4 of 21; 95% CI, 5-42) and a bilineage (HI-E and HI-N) response rate of 20% (4 of 20; 95% CI, 6-44) in patients with anemia and neutropenia.…”
Section: Efficacymentioning
confidence: 96%
See 1 more Smart Citation
“…TLK199 (ezatiostat hydrochloride; Telintra, Patheon, Inc., Mississauga, Ontario, Canada) is currently being tested for the treatment of myelodysplastic syndrome (MDS), a bone marrow neoplastic disease characterized by an ineffective production or dysplasia of myeloid blood cells and a risk of transformation into acute myeloid leukemia (AML). 55,56 GSTP1-1 is polymorphic. In humans, the GSTP1 gene has been mapped to chromosome 11q13, and four allelic variants have been described: GSTP1*A (wild-type Ile 105, Ala 114), GSTP1*B (Val 105, Ala 114), GSTP1*C (Val 105, Val 114), and GSTP1*D (Ile 105, Val 114).…”
Section: Gsh Analogsmentioning
confidence: 99%
“…Ezatiostat hydrochloride: is a glutathione S-transferase P1-1 inhibitor, evaluated in myelodysplastic syndrome. In a phase I/II study 47 , trilineage responses were observed in 4 of 16 patients (25%) with trilineage cytopenia. These responses were accompanied by improvement in clinical symptoms and reductions in transfusion requirements.…”
Section: Other Agents In Early Clinical Developmentmentioning
confidence: 99%